Pendidikan Xaverius Pada Masa Belanda di Indonesia - Andika - Juliansyah; Adittya Roll Asmi; Aulia Novemy Dhita (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
Education should be intended for all levels of society regardless of specific classes and groups. Education in the past has the aim of forming a person with the spirit of a knight based on noble character, but when the colonial occupation is introduced, a modern education system teaches reading and writing with the aim to produce quality workers with low wages. When applied the ethical policy, the goal of education is to change direction with the aim of advancing and improving people's lives. Through this educational channel, deliberately by Franz van Lith, a Jesuit who chose a missionary workshop through the education channel Franz van Lith thought that if If you want to give a Catholic faith, you must first change the mindset and prosperity of the Javanese people and the only right way is through education. Franz van Lith had several ideas that education should be enjoyed by anyone without forgetting where students came from. The idea gradually became an educational concept that was valid until later years. The problems examined in this study include (1) Xaverius's education in the Dutch period (2) What background did van Lith introduce modern education to the Javanese community in the Muntilan region? (3) How did the colonial government respond to the establishment of modern education by van Lith? ? : (4) How is the concept of education of Xaverius College tabun 1900-19422 In writing a research requires a method because the method is a process and procedure taken to obtain a validity in research The research method aims to answer the problems faced in research The method There are four methods used in this research, namely collecting sources, criticizing sources, interpreting sources and writing based on sources in accordance with the facts. the establishment of Xaverius College was constrained by the fact that there were restrictions on subsidies for private schools Over time the policy of limiting subsidies was abolished and Xavmius College received assistance from the Dutch Colonial government The teachers and teachers at Xaverius College were Brother Priests and school alumni who have the necessary skills Subjects at Xaveius College are intended for all students and some are classified according to classification as schools that have questions about the Katolsk religion, Xaverius College always conducts religious celebrations. Students who are not Catholic are not forced to embrace Catholicism.